Pengaruh Kualitas Pelayanan dan Komunikasi Terapeutik Terhadap Kepuasan Pasien Rawat Jalan di Puskesmas Pabuaran Indah Kecamatan Cibinong Kabupaten Bogor - Iis Maelani; Adriza; Widya Nengsih (Economic Reviews Journal, 2025)
The study aims to determine the influence of service quality and therapeutic communication on outpatient satisfaction at Pabuaran Indah Public Health Center, Cibinong District, Bogor Regency. This research employed a quantitative approach with a survey method, using data collection techniques including observation, interviews, questionnaires, and documentation studies. The sample consisted of all outpatient visitors during May–June 2024, 100 patients, selected using the census technique. The results show that the service quality is categorized as good, with an average score of 3.95. Service quality has a moderate relationship with patient satisfaction, indicated by a correlation coefficient (R) of 0.587 and a determination coefficient (R²) of 0.345, meaning that 34.5% of patient satisfaction is influenced by service quality. Therapeutic communication, also rated as good with an average score of 3.88, shows a strong relationship with patient satisfaction, with a correlation coefficient (R) of 0.744 and a determination coefficient (R²) of 0.553, indicating that 55.3% of patient satisfaction is influenced by therapeutic communication. Simultaneously, service quality and therapeutic communication have a strong relationship with patient satisfaction, with a correlation coefficient (R) of 0.709 and a determination coefficient (R²) of 0.509, meaning that both variables together influence 50.9% of patient satisfaction. In conclusion, service quality and therapeutic communication have a significant influence both partially and simultaneously on outpatient satisfaction at Pabuaran Indah Public Health Center.